Work engagement pada jurnalis: Bagaimana peranan quality of work life? - Arini Isyfa Salsabila; Diah Sofiah; Yanto Prasetyo (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to explain the relationship between quality of work life and work engagement in journalists. The subjects in the study were journalists from a combination of several media companies including Koran Madura, Radar Madura, and Radio Republik Indonesia (RRI) totaling 89 people. The data analysis technique in this study used product moment analysis. Based on the results of the study, the value of rxy = 0.646 with p = 0.000 (p <0.01) means that there is a significant positive relationship between quality of work life and work engagement in journalists. Keywords: Quality of Work Life, Work Engagement, Journalist.